How local autonomy was lost a history of stevedoring at Fremantle, 1880 to 1950. - Fletcher, Thomas A. (Curtin University, 1998)
This thesis examines how the stevedoring industry at Fremantle was absorbed into a national framework of port cargo-handling services during the first half of the twentieth century. The process of change compelled a local industry with its own peculiarities to conform to standards imposed by central authorities with priorities which were not necessarily in harmony with local practice or custom.In part this was the result of the inexorable forces released by Federation. After the creation of the Commonwealth, there was no isolation for anyone from the Commonwealth government's powers to legislate change if it was deemed to be in the national interest. Power, therefore, would flow towards central authorities: for the shipowners and their stevedores this meant to a central organisation, the Association of Employers of Waterside Labour (AEWL); for the labourers it meant, eventually, to the national executive of the Waterside Workers Federation (WWF).The Commonwealth government had the power and the will to intervene in stevedoring when the national interest dictated. The Commonwealth Conciliation and Arbitration Court started the process in 1914. The Commonwealth government in the War of 1914-18, in 1928, made further inroads into curtailing the levels of local autonomy. In the 1939-45 War the process was completed by the creation of government stevedoring industry commissions and boards. The final impact to local autonomy came in 1950 when the policies of a new conservative Commonwealth government forced the Fremantle Lumpers Union to seek the protection of a national union, the WWF.This thesis follows the path taken by the Fremantle stevedoring industry on its way to complete integration and absorption into the national port cargo-handling service. It examines the resistance to the changes brought about by centralisation and the part played in that struggle by both employers and employees at Fremantle to retain some control over their respective destinies.